PENGARUH METODE LATIHAN DRIBBLING ZIG-ZAG DAN DRIBBLING SHUTTLE RUN TERHADAP KUALITAS DRIBBLING PEMAIN SSB GANESHA PUTRA PURWODADI KELOMPOK UMUR 13-14 - Hernanda Pramudya Laksito; Dhias Fajar Widya Permana (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2026)
This study aims to examine the effect of zig-zag and shuttle run dribbling training methods on the dribbling performance of 13–14-year-old players at SSB Ganesha Putra Purwodadi. Dribbling is a key fundamental skill in football that should be developed from an early age. The research used a quantitative approach with a quasi-experimental design (pretest-posttest two group design). A total of 20 players were divided into two groups and trained over 16 sessions during a four-week period. The instrument used was a dribbling test conducted before and after the intervention. Data were analyzed using paired sample t-tests and independent sample t-tests with SPSS. The results showed that both training methods significantly improved dribbling quality (p < 0.05). The zig-zag group improved by an average of 1.06 seconds (5.93%), while the shuttle run group improved by 0.68 seconds (3.79%). Based on the findings, it can be concluded that the zig-zag training method is more effective than the shuttle run method in enhancing players’ dribbling skills. The zig-zag drill focuses on rapid direction changes, agility, and coordination, which are crucial in football gameplay. This study is expected to serve as a reference for coaches in designing effective training programs and contribute to the development of technical training methods football.